From diagnosis to routine care in type 1 diabetes in children: Parents' experiences - Géraldine Heilporn; Maude Laberge; André Côté; Monia Rekik (The Beryl Institute, 2019)
Having a child who lives with a Type 1 Diabetes (T1D) can represent a high burden for parents. The objective of our study is to identify and analyze the main challenges expressed by parents so that health care services better meet the needs of parents of T1D children. Semi-structured interviews were conducted with parents of 19 T1D children regarding detection and diagnosis, initial management at the hospital, post-discharge adaptation including daycare or school reintegration, and long-term T1D monitoring. Data analysis was performed following an inductive approach. The results showed a lack of knowledge regarding T1D in the society, especially for parents and educators. Furthermore, most parents felt overwhelmed at the hospital, and not ready for the intense self-management education (SME). They suggested it could be split over an extended period and discussed from a more practical perspective. Parents' burden is highest in the post-discharge adaptation stage especially for school reintegration, management of blood glucose levels and calculation of carbohydrates. Finally, returning to a social life was difficult, but contacts with diabetic families was a relief. In conclusion, the SME ought to be flexible and adapted to parents' needs. Spreading it over a longer period would ease families' experience. Efforts should also be made to alleviate the parents' burden on the post-discharge adaptation perceived as the most difficult stage, especially for school reintegration where training and resources on T1D should be given to key staff. Public education campaigns would raise awareness and ensure better knowledge of T1D by general population. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.